Panama's economic development: the role of agriculture - Merrill, William Charles (Ames : Iowa State University Press, 1975)
This book is about the Panama economic growth and performance
With bibliographical index
Bibliography: p. 213-216.
oo 06/8/18
Loans
Keywords: Agriculture; Agriculture and state